2006
DOI: 10.1007/s11106-006-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of predictable secondary structures in materials for high-temperature bearings

Abstract: 621.762The composition of secondary structures that develop on the surface of high-temperature composite materials based on steel R6M5F3 scraps with a CaF 2 admixture is investigated under friction at a slip speed of 1 m/sec, load of 7 MPa, and heating temperature of up to 600°C in air. The possibility of predicting and controlling functional properties of bearing materials by selection of initial components that provide for development of friction films of the required thickness and composition is demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This resulted in a multivariant synergetic system characterized by nonlinear internal processes, specific peaking modes [9][10][11], and, as a consequence, at least two stable states in direct relationship with operating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in a multivariant synergetic system characterized by nonlinear internal processes, specific peaking modes [9][10][11], and, as a consequence, at least two stable states in direct relationship with operating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It was confirmed that, the wear mechanism of antifriction composites depends not only on the material's initial properties, but also to a large extent on the properties of the formed antifriction films, the so-called secondary structures [9][10][11]. When applied, solid lubricants contribute to the constant and uniform lubrication of contact surfaces at high temperatures due to their ability to soften and spread over the entire contact surface, which simultaneously protects the surface from oxidation [12,13]. The friction film was formed during the operation and greatly affects the behavior of high-temperature friction units.…”
Section: Introductionmentioning
confidence: 97%
“…The friction processes analysis shows that the wear rate of the friction surfaces is determined by the properties of the formed separating antifriction films (so called secondary structures) and depends on their nature [5]- [7]. The films on the contact surfaces can have a positive effect, minimizing the frictional forces and preventing the adhesion of the bearing and shaft, and a negative impact, when the friction film acts as abrasive depending on the working conditions.…”
Section: Introductionmentioning
confidence: 99%